2012
DOI: 10.5402/2012/379081
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Evaluation of Cell Cycle Regulators: Impact on Predicting Prognosis in Stage T1 Urinary Bladder Cancer

Abstract: Background and Objective. The cell cycle is regulated by proteins at different checkpoints, and dysregulation of this cycle plays a role in carcinogenesis. Matrix metalloproteinases (MMPs) are enzymes that degrade collagen and promote tumour infiltration. The aim of this study was to evaluate the expression of various cell cycle regulators and MMPs and to correlate such expression with progression and recurrence in patients with stage T1 urothelial carcinoma of the bladder (UCB). Patients and Methods. This pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
3
11
0
Order By: Relevance
“…However, data were inconsistent showing CyclinD1 expression as a marker of adverse [20][21][22] or favorable [23][24][25][26][27] prognosis or without prognostic impact. 28 Only two studies investigated the prognostic relevance of CCND1 amplification in bladder cancer: while CCND1 amplification was an adverse risk factor in non-muscle invasive bladder cancers, 29 it failed to predict survival in muscle invasive tumors. 30 Finally, CyclinD1 expression has been shown to predict response to chemotherapies in cancers of the head and neck; 10,11 however, this potential has never been tested in bladder cancer.…”
mentioning
confidence: 99%
“…However, data were inconsistent showing CyclinD1 expression as a marker of adverse [20][21][22] or favorable [23][24][25][26][27] prognosis or without prognostic impact. 28 Only two studies investigated the prognostic relevance of CCND1 amplification in bladder cancer: while CCND1 amplification was an adverse risk factor in non-muscle invasive bladder cancers, 29 it failed to predict survival in muscle invasive tumors. 30 Finally, CyclinD1 expression has been shown to predict response to chemotherapies in cancers of the head and neck; 10,11 however, this potential has never been tested in bladder cancer.…”
mentioning
confidence: 99%
“…Another study interpreted p16 expression below 5% as negative staining for p16 [1]. Some authors regarded expression loss (no staining) and overexpression (staining > 50%) as abnormal and moderate staining as normal [21][22][23][24]. Four of the scoring methods employed in these studies were also used in our work for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, there was a statistically significant association between recurrence and p16 expression only when the p16d scoring system was used. Olsson et al [23] also used the same staining pattern (p16d) in stage T1 urinary bladder cancers and they detected normal p16 expression was related to a lower risk of tumor progression. Similar to our study, Lee et al [21] investigated four cell cycle proteins (p16, pRb, p53, cyclin D1) and found no correlation between progression and p16 (p16d method) expression; their results suggested that multiple genetic defects affected the clinical course and metastatic capacity of bladder carcinomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 15-70% of pT1 tumors relapse within a year after transurethral resection and 7-44% of these tumors are likely to progress into muscle in five years (2).…”
Section: Introductionmentioning
confidence: 99%